Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s00403-006-0725-6
|View full text |Cite
|
Sign up to set email alerts
|

Strong expression of a longevity-related protein, SIRT1, in Bowen’s disease

Abstract: The class III histone deacetylase (HDAC), SIRT1, is a mammalian homologue of the Saccharomyces cerevisiae chromatin-silencing factor Sir2 that regulates longevity. SIRT1 regulates cell survival via deacetylation of p53 and forkhead transcription factors, and overexpression of SIRT1 is reported to be essential for cell growth and survival in some kinds of cancer. To elucidate the role of SIRT1 in human skin carcinogenesis, we have examined SIRT1 protein expression in 20 cases each of squamous cell carcinoma (SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 17 publications
3
113
0
1
Order By: Relevance
“…SIRT1 is overexpressed in acute myeloid leukemia (AML) blasts from patients as well as AML cell lines (Bradbury et al, 2005). The overexpression found in multiple types of nonmelanoma skin cancers, including early stages, suggests that SIRT1 may be playing a critical role in promoting proliferation in skin cancer (Hida et al, 2006). The ability of cancer cells to undergo senescence correlates with their response to treatment.…”
Section: Sirt1 Promotes Replicative Senescence During Prolonged Exposmentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT1 is overexpressed in acute myeloid leukemia (AML) blasts from patients as well as AML cell lines (Bradbury et al, 2005). The overexpression found in multiple types of nonmelanoma skin cancers, including early stages, suggests that SIRT1 may be playing a critical role in promoting proliferation in skin cancer (Hida et al, 2006). The ability of cancer cells to undergo senescence correlates with their response to treatment.…”
Section: Sirt1 Promotes Replicative Senescence During Prolonged Exposmentioning
confidence: 99%
“…Tumor cells show global changes in their chromatin, which can in part be due to the dysregulation of sirtuins (Jones and Baylin, 2007). Overexpression of SIRT1, SIRT2, SIRT3 and SIRT7 are found in tumors (De Nigris et al, 2002;Hiratsuka et al, 2003;Bradbury et al, 2005;Ashraf et al, 2006;Hida et al, 2006), indicating that sirtuin inhibitors may be useful chemotherapeutic agents against cancers that overexpress these sirtuins. The increased acetylation of targets, such as p53, Foxo, Ku70 and BCL6 induced by inhibition of sirtuins, in conjunction with chemotherapy agents that damage DNA, might induce tumor cell apoptosis.…”
Section: Therapeutic Potential Of Sirtuin Regulationmentioning
confidence: 99%
“…In our study, significantly elevated expression of sIrt1 was observed in HCC tissues when compared to non-tumor tissues. Increased expression of sIrt1 has been reported in various types of malignant tumors, including human cutaneous tumors (12), and breast (13), colon (13), prostate (14), and mouse cancers (9). In addition, sIrt1 expression has been suggested as a possible prognostic indicator in human malignant lymphoma (16) and gastric cancer (22).…”
Section: Of ---------------------------------------mentioning
confidence: 99%
“…Up-regulation of sIrt1 induces deacetylated inactivation of p53, which allows proliferation of cells in the presence of damaged DNA such that mutations accumulate, including those in p53 itself, leading to disruption of the cell cycle control and promotion of tumor progression (6)(7)(8)(9)(10)(11). recent studies have demonstrated overexpression of sIrt1 in cancer tissue, compared with normal tissue, suggesting that sIrt1 may act as a tumor promoter (9,(12)(13)(14)(15)(16). However, expression of sIrt1 in HCC and its role have not been investigated.…”
mentioning
confidence: 99%
“…Accumulating evidence also point to SirT1 as having a function in cancer; however, inferences from the literature are that SirT1 has both oncogenic and tumor-suppressor activities. SirT1 was reported to be overexpressed in acute myeloid leukemia, non-melanoma skin cancer, breast cancer, colorectal carcinoma and prostate cancer (Bradbury et al, 2005;Kuzmichev et al, 2005;Hida et al, 2007;Huffman et al, 2007;Stunkel et al, 2007) and to be downregulated in glioblastoma, prostate cancer, bladder carcinoma, breast cancer, hepatocellular carcinoma and ovarian cancer (Wang et al, 2008a). It is also expressed at a high level in diffuse large B-cell lymphomas and is associated to bad prognosis (Jang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%